EFEKTIVITAS BANNER SEBAGAI MEDIA PROMOSI KESEHATAN 3M PENCEGAHAN COVID-19 OLEH GUGUS TUGAS PERCEPATAN PENANGANAN COVID-19 DI PUSKESMAS CURUG KABUPATEN TANGERANG - Noninda Oki Rianatasha (2021)
Covid-19 cases in Indonesia have continued to increase since the beginning of the pandemic. Curug District is a district with the highest Covid-19 cases in Tangerang Regency. Outdoor health promotion by using banner media is one of the ways that the Covid-19 Handling Acceleration Task Force to control the increase in cases that have occurred. The purpose of this study was to assess the effectiveness of the banner media used by the Task Force for the Acceleration of Handling Covid-19 in health promotion for 3M Covid-19 prevention in the work area of the Curug Health Center. This study used a survey study design with a total sample of 234 people who were taken using the accidental sampling method. The results showed that 89.7% of the public had received health promotion by means of banners and as many as 69.2% of the people had complied with the 3M protocol for preventing Covid-19. The results of the bivariate test analysis using the chi-square test showed a p-value of 0.007, which means that there is a significant relationship between health promotion using banner media and the compliance of the Curug Community Health Center working area with the 3M health protocol to prevent Covid-19. Based on these results, health promotion using banner media carried out by the Task Force for the Acceleration of Handling Covid-19 is effective in an effort to prevent the spread of Covid-19 in the work area of the Curug Health Center and people who do not get health promotion with banner media have a 2,667 times risk of not complying. the 3M Covid-19 Prevention health protocol.